X-ray Structures of the Hexameric Building Block of the HIV Capsid - Pornillos, Owen (2009)
The mature capsids of HIV and other retroviruses organize and package the viral genome and its associated enzymes for delivery into host cells. The HIV capsid is a fullerene cone: a variably curved, closed shell composed of approximately 250 hexamers and exactly 12 pentamers of the viral CA protein. We devised methods for isolating soluble, assembly-competent CA hexamers and derived four crystallographically independent models that define the structure of this capsid assembly unit at atomic resolution. A ring of six CA N-terminal domains form an apparently rigid core, surrounded by an outer ring of C-terminal domains. Mobility of the outer ring appears to be an underlying mechanism for generating the variably curved lattice in authentic capsids. Hexamer-stabilizing interfaces are highly hydrated, and this property may be key to forming quasi-equivalent interactions within hexamers and pentamers. The structures also clarify the molecular basis for capsid assembly inhibition, and should facilitate structure-based drug design strategies.